Banning telecommuting at Yahoo! - ANG, Jovina (Institutional Knowledge at Singapore Management University, 2013)
This case is set in February 2013, when several disgruntled Yahoo employees immediately leaked a confidential memo that had arrived from the human resources department, advising them of a telecommuting ban that was to be imposed in June that year. The memo became a hot item in traditional and social media as soon as it was released. Apparently, this new policy would impact around 200 of Yahoo’s 12,000 employees. There were strong responses from many people – both from within and outside Yahoo, criticising the new policy and Marissa Mayer, the recently appointed CEO. This new policy was clearly bucking the telecommuting trend of the 21st century workplace. However, Mayer was clear that the policy was needed to bring about innovation and a culture of communication and collaboration, that could drive great ideas absolutely crucial for Yahoo’s success. How could Mayer leverage her leadership towards capturing employee trust and redressing the negative sentiment that had come about from the telecommuting ban? What could Mayer do to signal the company’s cultural reboot and win employee buy-in for the new policy and trust? And if she had delivered the policy differently, would she have avoided all the negative press? This case provides an opportunity for students to learn about effective communication and leadership. It explores current management issues such as execution of rapid organisational and cultural transformation, and covers aspects of successful leadership. This case also touches on a framework for delivering an effective negative message and a new policy, and explores strategy that can be adopted to obtain employee buy-in and regaining trust.